2020
DOI: 10.3390/cells9040836
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sialic Acid-Binding Immunoglobulin-Type Lectins in Fish Reveals Teleost-Specific Structures and Expression Patterns

Abstract: The cellular glycocalyx of vertebrates is frequently decorated with sialic acid residues. These sialylated structures are recognized by sialic acid-binding immunoglobulin-type lectins (Siglecs) of immune cells, which modulate their responsiveness. Fifteen Siglecs are known to be expressed in humans, but only four Siglecs are regularly present in fish: Siglec1, CD22, myelin-associated glycoprotein (MAG), and Siglec15. While several studies have dealt with the physiological roles of these four Siglecs in mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The data analysis was performed using Kaluza software, ver. 1.2 (Beckman Coulter) ( Löhrke et al, 2010 ; Bornhöfft et al, 2020 ). All analyses were performed on samples from three donors for each synovial tissue source and each breed ( n = 3 independent biological replicate).…”
Section: Methodsmentioning
confidence: 99%
“…The data analysis was performed using Kaluza software, ver. 1.2 (Beckman Coulter) ( Löhrke et al, 2010 ; Bornhöfft et al, 2020 ). All analyses were performed on samples from three donors for each synovial tissue source and each breed ( n = 3 independent biological replicate).…”
Section: Methodsmentioning
confidence: 99%
“…1 A), since the IgV domain and residue R143 of Siglec-15 are sufficient to mediate sialylated glycan binding. 8 , 33 To generate anti-Siglec-15 mAbs, mice immunized with high-affinity antibodies were selected for the cell fusion experiment. After 2 rounds of selection by ELISA, the best candidate was identified based on its high binding affinity for Siglec-15.…”
Section: Resultsmentioning
confidence: 99%
“…We generated a single substitution mutation, R143A, in Siglec-15 to facilitate mAb screening (Fig. 1A), since the IgV domain and residue R143 of Siglec-15 are sufficient to mediate sialylated glycan binding 8,33. To generate anti-Siglec-15 mAbs, mice immunized with high-affinity antibodies were selected for the cell fusion experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Given their ability to selectively recognize and bind the carbohydrate moiety of glycoconjugates, one of the most prominent physiological function of lectins in marine organisms is their role as potent defense molecules where they are involved in processes such as non-self-recognition, inflammation, opsonization, phagocytosis, encapsulation, and lysis of foreign cells [ 111 , 112 ]. The ability of lectins to trigger multiple immunological responses is essential for autoimmunity and management of infection in fish [ 63 , 72 , 86 , 113 ]. For instance, the lily type lectins, CsLTL-1 and CsLTL-2, are crucial immune genes in stripped murrel Channa striatus for selectively recognizing and eliminating pathogens by disrupting the cell membrane [ 113 , 114 ].…”
Section: Physiological Functions Of Lectins In Host Bodymentioning
confidence: 99%
“…For instance, the lily type lectins, CsLTL-1 and CsLTL-2, are crucial immune genes in stripped murrel Channa striatus for selectively recognizing and eliminating pathogens by disrupting the cell membrane [ 113 , 114 ]. Recently, sialic acid-binding immunoglobulin-type lectins (Siglec1, CD22, myelin-associated glycoprotein (MAG), and Siglec15) in pikeperch ( Sander lucioperca ), rainbow trout ( Oncorhynchus mykiss ) and maraena whitefish ( Coregonus maraena ) influenced the cellular reactivity against damage-associated molecular patterns (DAMPs) [ 63 ]. Brinchmann et al [ 115 ] reported that fish mucosal lectins could trigger agglutination, inhibition of bacterial chemotaxis, endocytosis, phagocytosis, as well as inhibition of pathogens.…”
Section: Physiological Functions Of Lectins In Host Bodymentioning
confidence: 99%